THE ROLE OF ADULT STUDENT’S INDIVIDUALITY IN OPTIMIZATION OF EDUCATIONAL PROCESS - Serheieva, Olha (The Modern Higher Education Review, 2019)
The article outlines the main criteria for determining the temperament of the student for the formation of educational groups in order to optimize the educational process. It describes the way of conducting research to identify the effectiveness of training students with a predominant phlegmatic type of temperament (introverts) and students with a predominant choleric type of temperament (extroverts) in separate academic groups. The article also touches upon the problem of the right to have a mistake as the only way to the educational growth of a person. The main results of the study are pointed out.